Influence of Psychosocial Problems on Healthy Life Style Among Pregnant Women - Sanaa Hussain Obaid, Nuha Adel Ebraheim (Pakistan Journal of Medical & Health Sciences, 2022)
Because of its combined influence on the fetus/newborn and the mother, maternal mental health is an important public health concern around the world. This study was a descriptive study (quantitative design) that was conducted among pregnant women in Baghdad city. It comprised 150 pregnant women who attended the hospital. The data was collected utilizing the specified questionnaire after validity and reliability were assessed by (12) experts, as well as the structured interview technique with persons who were individually interviewed. The findings indicated that social problem affect pregnant women of various ages and education, The frequency of previous abortions was associated with an increase in psychosocial difficulties such as social problems. It was concluded that psychosocial issues during pregnancy could have an impact on the mother’s lifestyle and behavior.